Aeromonas hydrophìla, A human pathogen - ABRAHIM (Α. ΑΜΠΡΑΧΙΜ) A.; PAPANOTAS (Κ. ΠΑΠΑΝΩΤΑΣ) K. (Journal of the Hellenic Veterinary Medical Society, 2018)
Aeromonas hydrophìla has been considered human pathogen and is involved in gastroenteritis, wound infections and septicaemia. It is also a cause of disease in fish, in amphibian and in reptiles. A. hydrophìla can grow in chilled foods and has been isolated from the environment, from non chlorinated and chlorinated water, ready-to-eat meat from poultry meat, fish and fish products, raw milk and milk products and vegetables. The present article is a review article and deals with the isolation and identification procedures, pathogenesis and epidemiology of the microorganism and the therapy to humans.